Answer:
Step-by-step explanation:
Answer:
฿₹Ø: 1391 US$
Step-by-step explanation:
Answer:
A) x = 0, 2
Step-by-step explanation:
(x + 4) / 6x = 1 / x
this is a proportion, so you can cross-multiply and get:
x(x + 4) = 6x
x² + 4x = 6x
x² - 2x = 0
x(x - 2) = 0
x = 0
x - 2 = 0 so, x = 2
Answer: Choice D. y = (x-1)^2 - 3
The vertex is (h,k) = (1,-3). So h = 1 and k = -3.
We have a = 1 as the leading coefficient.
Plug those values into the equation below
y = a(x-h)^2 + k
y = 1(x - 1)^2 + (-3)
y = (x - 1)^2 - 3
Ln(56) = 4x-9
ln(56) + 9 = 4x
(ln(56) + 9)/4 = x